The impact of rendered protein meal oxidation level on shelf-life, sensory characteristics, and acceptability in extruded pet food - Chanadang, Sirichat; Koppel, Kadri; Aldrich, Greg C. (My University, 2017)
Pet foods are expected to have a shelf-life for 12 months or more. Sensory analysis can be used to determine changes in products and to estimate products’ shelf-life. The objectives of this study were to (1) investigate how increasing levels of oxidation in rendered protein meals used to produce extruded pet food affected the sensory properties and (2) determine the effect of shelf-life on pet owners’ acceptability of extruded pet food diet formulated without the use of preservative. Pet food diets contained beef meat bone meal (BMBM) and chicken byproduct meal (CBPM) in which the oxidation was retarded with ethoxyquin, mixed tocopherols, or none at all, and then extruded into dry pet foods. These samples represented low, medium, and high oxidation levels, respectively. Samples were stored for 0, 3, 6, 9, and 12 months at ambient temperature. Each time point, samples were evaluated by six highly trained descriptive panelists for sensory attributes related to oxidation. Samples without preservatives were chosen for the acceptability test, since the differences in sensory characteristics over storage time were more distinguishable in those samples. Pet owners evaluated samples for aroma, appearance and overall liking. Descriptive sensory analysis detected significant changes in oxidized-related sensory characteristics over storage time. However, the differences for CBPM samples were more pronounced and directional. The consumer study showed no differences in pet owners’ acceptability for BMBM samples. However, the noticeable increase in aroma characteristics (rancid aroma 0.33-4.21) in CBPM samples over storage time did have a negative effect on consumer’s liking (overall liking 5.52-4.95). © 2016 by the authors; licensee MDPI, Basel, Switzerland.
Citation: Chanadang, S., Koppel, K., & Aldrich, G. (2016). The impact of rendered protein meal oxidation level on shelf-life, sensory characteristics, and acceptability in extruded pet food. Animals, 6(8). doi:10.3390/ani6080044
Keywords: Aroma; Beef Meat And Bone Meal; Chicken Byproduct Meal; Rancidity